Avaliação dos parâmetros clínicos e laboratoriais de bezerros com diarréia neonatal naturalmente adquirida - Moises Dias Freitas (2009)
The creation of calves is one of the most difficult stages in production of dairy cattle, because the high costs of labor-power exacerbated by high mortality. At this stage, the neonatal diarrhea constitute the main group of diseases, for multifactorial origin often leading to dehydration, acidosis and electrolyte imbalances. This work had as main objective to establish the profile of hydroelectrolytic disorders and acid-basic, caused by naturally occurring diarrhea in calves reared in the field house tropical systems. It was observed mainly in calves with diarrhea the presence of compensated metabolic acidosis with hyponatremia, hyperkalemia, hypoglycemia, increased serum concentration of urea and fall of urinary pH